1995
DOI: 10.1111/j.1476-5381.1995.tb17232.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the binding of [3H]‐mepyramine to intact human U373 MG astrocytoma cells: evidence for histamine‐induced H1‐receptor internalisation

Abstract: 1 The kinetics of the binding of 5 nM [3Hl-mepyramine to sites on intact human U373 MG astrocytoma cells, sensitive to inhibition by 2 gM pirdonium, were temperature-dependent. At 370C the half-time for association was 0.9 ±0.4 min and at 40C 19±3 min. Dissociation of bound [3H]-mepyramine was fast at 370C, tO.5 1.5 +0.3 min, but at 60C dissociation initiated by dilution or addition of unlabelled mepyramine was negligible over 120 min. The very slow dissociation at 60C made it possible to reduce the level of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…High and low affinity sites for olopatadine, epinastine, or fexofenadine showed exactly the same difference observed between tertiary amine antagonists and their quaternary derivatives, including pirdonium and norpirdonium (17), yet the percentage of the binding of [ 3 H]mepyramine insensitive to inhibition is approximately the same, irrespective of whether the antagonists are tertiary or quaternary amines (17) or sedative or non-sedative (Table 1). This suggests that the secondary site is intracellular, but there is only sufficient intracellular compound for inhibition to be observed during the experiment at higher extracellular concentrations of antagonist.…”
Section: Two Types Of Displacement Curves For Non-sedative H 1 -Recepmentioning
confidence: 66%
See 2 more Smart Citations
“…High and low affinity sites for olopatadine, epinastine, or fexofenadine showed exactly the same difference observed between tertiary amine antagonists and their quaternary derivatives, including pirdonium and norpirdonium (17), yet the percentage of the binding of [ 3 H]mepyramine insensitive to inhibition is approximately the same, irrespective of whether the antagonists are tertiary or quaternary amines (17) or sedative or non-sedative (Table 1). This suggests that the secondary site is intracellular, but there is only sufficient intracellular compound for inhibition to be observed during the experiment at higher extracellular concentrations of antagonist.…”
Section: Two Types Of Displacement Curves For Non-sedative H 1 -Recepmentioning
confidence: 66%
“…Human U373 MG astrocytoma cells (National Culture Collection, Porton Down, UK) were cultured in 150-cm 2 culture flasks as described previously (17). Dissociated cells were suspended in normal HEPES buffer (120 mM NaCl, 5.4 mM KCl, 1.6 mM MgCl 2 , 1.8 mM CaCl 2 , 11 mM D-glucose, and 25 mM HEPES, pH 7.4 at 37°C) and kept at 37°C for 30 min for equilibration.…”
Section: Cell Preparation For Intact Cell Binding Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…H 1 and H 2 receptors have been reported in both native astrocytes and in astrocytoma cell lines (12)(13)(14)29). Using the selective antagonists of the different histamine receptors, we showed that the H 1 receptor is involved.…”
Section: Discussionmentioning
confidence: 93%
“…Histamine binds to three types of membrane receptors: H 1 receptors, usually coupled to phospholipase C activation and internal Ca 2ϩ mobilization; H 2 receptors, connected with adenylate cyclase; and H 3 receptors, controlling histamine turnover and release (11,21). Astrocytes as well as astrocytoma cell lines have been demonstrated to express both H 1 and H 2 histamine receptors (12,13,14,29). Stimulation of H 1 receptors results in an increased intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) in glioma cells, caused by an initial transient phase of Ca 2ϩ mobilization from intracellular stores and a second sustained phase mediated by Ca 2ϩ influx (1,10,24,25,31,41,43).…”
mentioning
confidence: 99%